Educational Financing Management in Tarekat–based Pesantren - Priatna, Tedi; Nurhamzah, Nurhamzah; Ratnasih, Teti; Siregar, Hariman Surya (Jurnal Pendidikan Islam, 2018)
This paper aims to identify the financing management in a pesantren in Tasikmalaya, Indonesia. The study employed a qualitative approach employing a case study. The data collection techniques used in this study were in-depth interview, observation, and literature study. The research was conducted at Pesantren Tarekat al-Idrisiyyah Tasikmalaya, West Java, Indonesia and it found several findings: First, the source of financing came from the santri (pesantren students), government grant, social donation and auction from jamaah (communities), and pesantren business unit. Second, the financing plan of pesantren was prepared and established in the form of RKP (Rapat Kerja Pesantren/Pesantren Budget Plan) through Rakernas (Rapat Kerja Nasional/National Summit). Third, the implementation of financing included the receipt and expenditure of funds record. Fourth, evaluation and financial accountability took place as reflection of good financial management. When financing management was done professionally in spending salaries, benefits, and purchase of infrastructure improvement, the impacts led to pesantren achievements both in academic and non-academic fields.